A New Dibenzocyclooctadiene Lignan from the Stems of Schisandra neglecta and It Cytotoxicities - Ye, Yan-Qing; Xia, Cong-Fang; Li, Yin-Ke; Wu, Xian-Xue; Du, Gang; Hu, Qiu-Fen; Gao, Xue-Mei (Asian Journal of Chemistry, 2014)
A new dibenzocyclooctadiene lignan, neglignan H (1) was isolated from the stems of Schisandra neglecta. The structures of (1) was elucidated by spectroscopic methods, including extensive 1D and 2D NMR techniques. Compound 1 was tested for its cytotoxicity against five human tumor cell lines (NB4, A549, SHSY5Y, PC3 and MCF7) and compound 1 exhibited modest cytotoxicity against NB4, A549 and MCF7 cell with IC50 values of 8.1, 7.4 and 6.7 μM, respectively.